Local delivery of siRNA-loaded calcium phosphate nanoparticles abates pulmonary inflammation - Frede, Annika (Nanomedicine, 2017)
The local interference of cytokine signaling mediated by siRNA-loaded nanoparticles might be a promising new therapeutic approach to dampen inflammation during pulmonary diseases. For the local therapeutic treatment of pulmonary inflammation, we produced multi-shell nanoparticles consisting of a calcium phosphate core, coated with siRNAs directed against pro-inflammatory mediators, encapsulated into poly(lactic-co-glycolic acid), and coated with a final outer layer of polyethylenimine. Nasal instillation of nanoparticles loaded with a mixture of siRNAs directed against different cytokines to mice suffering from T(H)1 cell-mediated lung inflammation, or of siRNA directed against NS-1 in an influenza infection model led to a significant reduction of target gene expression which was accompanied by distinct amelioration of lung inflammation in both models. Thus, this study provides strong evidence that the specific and local modulation of the inflammatory response by CaP/PLGA nanoparticle-mediated siRNA delivery could be a promising approach for the treatment of inflammatory disorders of the lung.